Sycophancy and Dearth of Integrity in Governance - Okibe, Hyginus Banko (ESUT JOURNAL OF SOCIAL SCIENCES, 2020)
Sycophancy in governance occurs when performance of legitimate functions of government are erroneously exaggerated to invoke unwarranted stream of praises on a public officeholder or government in power. Critical observers describe it as deceitful, misleading and highly opinionated. It beguiles the masses to believe failed government actions, which a sycophant paints in different colours and thus makes governance wane significantly in integrity. It has become a predominant feature of democratic governance in Nigeria, hence, the study seeks to: (i) examine the trends of sycophantic behaviour in political leadership, (ii) ascertain the underlying factors that influence the behaviour, (iii) explain the consequences or its influence on governance, and (iv) proffer solutions to the problem. Accordingly, the study employs secondary data and content analysis to discuss the contending issues. Additionally, it adopts the “Theory of Planned Behaviour” to explain how sycophantic behaviour is formulated, nurtured and deliberately exhibited in pursuit of target objective, i.e. what inspires the interest or encourages the intention and what incentive that sustains the practice. The findings show that sycophancy has become deep-rooted in Nigeria governance system; it inflicts serious damage on regime integrity, and exposes both failures of political class and gullibility of the masses. It thus recommends political education, reorientation, inculcating objective political behaviour and tasking those vested with political power to live by their oaths of offices.